Multi layered Si-CuO quantum dots wrapped by graphene for high-performance anode material in lithium-ion battery - Rangasamy, Baskaran; Hwang, Jun Yeon; Choi, Wonbong (PERGAMON-ELSEVIER SCIENCE LTD, 2014)
Various approaches to improve the efficiency of Lithium ion batteries (LiB) by using Si have been suggested because Si has the highest known lithium capacity. Although Si is more than ten times higher capacity than existing graphite anodes, Si anodes have limited applications due to its high volume change during cycling. Here we demonstrated graphene/Si-CuO quantum dots (Gr/Si-CuO QD) layered structure as an efficient LiB anode which prevents large volume expansion of Si due to the presence of CuO-Cu3Si. By Electrophoresis Deposition technique, the multi-layer of graphene and Si-CuO QD has been successfully fabricated followed by annealing process to form Cu3Si interlayer as confirmed by High Resolution Transmission Electron Microscope-Energy Dispersive Spectroscopy, X-ray diffraction and Raman analyses. The annealed Gr/Si-CuO QD exhibit the initial gravimetric specific capacity of 2869 mAh g(-1) which is five times higher than that of annealed graphene at 0.5C. After 100 cycles at 1C rate the capacity retains similar to 71% and the excellent rate capability even at high C rate reveals controlled volume expansion owing to the multi layered architecture and the Cu3Si inter layer. The layered structure of Gr/Si-CuO QD electrode could be applied in next generation micro power sources. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: SILICON; CAPACITY; NANOSTRUCTURES